Paragorgia arborea - Schejter, L.; Genzano, G.; Pérez, C. D.; Acuña, F.; Cordeiro, R. T. S.; Silva, R. A.; Garese, A.; Bremec, C. S. (Zenodo, 2020)
Paragorgia arborea (Linnaeus, 1758) Material examined: BBB 2016: St. 13. Distribution: Western North Atlantic, East Canada to Cape Hatteras; Boreal Eastern Atlantic, northern Mid-Atlantic Ridge; Lusitanian-Mediterranean (Watling & Auster 2005); Norway to Nova Scotia, including Faroes Islands, Iceland and Greenland, 1330 m (Tendal 1992); off Crozet Islands, Indian Ocean (46°05’– 46°24.1’S, 49°37.0’– 50°37.1’E, 140–270 m) (Grasshoff 1979; D’Ambrosio et al. 1984); Aleutian Islands (Heifetz et al. 2005); Makarov Bay, Iturup Island, Sea of Okhotsk (Nedashkovskaya et al. 2005); Southern California (52°17’– 52°22’N, 160°40’– 160°34’E, 659–798 m), New Zealand (33°55’36”S– 52°17’22”S, 159°40’00– 177°54’30”E, 659–1525 m) (Sánchez 2005); Off Patagonia and Malvinas Islands (40°57’– 54°38’S, 56°52’– 63°00’W, 340– 1000 m) (Grasshoff 1979); Burdwood bank (54°31´S, 62°11´W, 330 m) (as Paragorgia sp.) (Auscavitch & Waller 2017); Drake Passage, 57°04´S, 67°30´W, 1400 m (as Paragorgia sp.) (Waller & Robinson 2011); off Staten Island (608 m) (present study). Remarks: According to Sánchez (2005), this species has a disjunct distribution between the Arctic and Antarctic, with no linking records. Auscavitch & Waller (2017) and Waller & Robinson (2011) cited Paragorgia sp. for the Drake passage and Burdwood bank, their identification at genus level is justified since the samplings were made by towed camera surveys. Deichmann (1936) said that according to Verrill (1922) this species is common off the fishing banks off Nova Scotia and Newfoundland. : Published as part of Schejter, L., Genzano, G., Pérez, C. D., Acuña, F., Cordeiro, R. T. S., Silva, R. A., Garese, A. & Bremec, C. S., 2020, Checklist of Benthic Cnidaria in the SW Atlantic Ocean (54 ºS- 56 ºS), pp. 201-239 in Zootaxa 4878 (2) on page 222, DOI: 10.11646/zootaxa.4878.2.1, http://zenodo.org/record/4424884 : {"references": ["Watling, L. & Auster, P. J. (2005) Distribution of deep-water Alcyonacea off the northeast coast of the United States. In: Freiwald, A. & Roberts, J. M. (Eds.), Cold-Water Corals and Ecosystems. Springer-Verlag, Berlin, pp. 279 - 296.", "Tendal, O. S. (1992) The North Atlantic distribution of the octocoral Paragorgia arborea (L., 1758) (Cnidaria, Anthozoa). Sarsia, 77, 213 - 217. https: // doi. org / 10.1080 / 00364827.1992.10413506", "Grasshoff, M. (1979) Zur bipolaren Verbreitung der Oktokoralle Paragorgia arborea (Cnidaria: Anthozoa: Scleraxonia). Senckenbergiana Maritima, 11 (3 / 6), 115 - 137.", "D'Ambrosio, M., Guerriero, A. & Pietra, F. (1984) Arboxeniolide- 1, a New, Naturally Occurring Xeniolide Diterpenoid from the Gorgonian Paragorgia arborea of the Crozet Is. (S. Indian Ocean). Zeitschrift fur Naturforschung C, 39 (11 - 12), 1180 - 1183. https: // doi. org / 10.1515 / znc- 1984 - 11 - 1232", "Heifetz, J., Wing, B. L., Stone, R. P., Malecha, P. W. & Courtney, D. L. (2005) Corals of the Aleutian Islands. Fisheries Oceanography, 14, 131 - 138. https: // doi. org / 10.1111 / j. 1365 - 2419.2005.00371. x", "Nedashkovskaya, O., Kim, S., Lysenko, A., Frolova, G., Mikhailov, V. & Bae, K. (2005) Bizionia paragorgiae gen. Nov., sp. nov., a novel member of the family Flavobacteriaceae isolated from the soft coral Paragorgia arborea. International Journal of Systematics and Evolutionary Microbiology, 55 (1), 375 - 378. https: // doi. org / 10.1099 / ijs. 0.63381 - 0", "Sanchez, J. A. (2005) Systematics of the bubblegum corals (Cnidaria: Octocorallia: Paragorgiidae) with description of new species from New Zealand and the Eastern Pacific. Zootaxa, 1014 (1), 1 - 72. https: // doi. org / 10.11646 / zootaxa. 1014.1.1", "Auscavitch, S. & Waller, R. (2017) Biogeographical patterns among deep sea megbenthic communities across the Drake Passage. Antarctic Science, 29 (6), 531 - 543. https: // doi. org / 10.1017 / S 0954102017000256", "Deichmann, E. (1936) The Alcyonaria of the western part of the Atlantic Ocean. Memoirs of the Museum of Comparative Zoology at Harvard, 53, 1 - 317.", "Verrill, A. E. (1922) Alcyonaria and Actinaria. Report of the Canadian Arctic Expeition, 8 (G), 1 - 164."]}